Integrated Reporting State Owned Enterprises: Trends, Theories, and Methodologies from Recent Literature - Anggun Trisnani; Rindu Rika Gamayuni; Nauli, Pigo (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to present a comprehensive mapping of the development of Integrated Reporting (IR) studies during the 2020–2025 period through a Systematic Literature Review (SLR) approach. This study identifies publication trends, methodological approaches, institutional contexts, and theoretical frameworks used in recent IR studies, with particular attention to research focusing on state-owned enterprises (SOEs). From the results of screening 1,390 documents indexed in the Scopus database, 42 articles met the inclusion criteria for further analysis. The findings show a significant increase in the number of IR publications since 2022, with a dominance of quantitative approaches and the use of stakeholder theory as the main conceptual basis. Research involving SOEs shows interesting dynamics, where developed countries emphasize governance and regulation, while developing countries tend to use IR as a means of legitimacy and transparency. This study concludes that IR continues to develop as a strategic reporting framework that bridges financial and non-financial aspects, with important implications for the public sector. These findings provide theoretical and practical contributions, and offer a relevant future research agenda, especially in the context of increasing SOE accountability.